Pengaruh Penggunaan Smartphone terhadap Perkembangan Personal Sosial Anak Usia Pra-Sekolah - Heni Heni; Ahmad Jalaludin Mujahid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of the use of smartphones on the personal social development of pre-school age children in Al-Marhamah Kindergarten. This research uses quantitative research methods with cross sectional design. The results showed more than half of pre-school age children are smartphone users with frequent frequency with 24 children (72.7%). Less than half of pre-school-aged children experience doubtful development with a total of 15 children (45.5%). Statistical test results obtained p value of 0.017. Conclusion, there is a significant relationship between smartphone usage and the personal social development of preschool children in Al-Marhamah, Majaelngka Regency, 2017. Keywords: Pre-School Age Children, Personal Development, Smartphones